2018
DOI: 10.1182/blood-2018-99-119861
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of Cobomarsen, an Inhibitor of Mir-155, in Cutaneous T Cell Lymphoma

Abstract: Background: Cobomarsen (MRG-106) is an inhibitor of miR-155, a microRNA with a strong link to cutaneous T cell lymphoma (CTCL) pathogenesis. The goals of this first in human study are to evaluate the safety, tolerability, pharmacokinetics, and efficacy of cobomarsen in mycosis fungoides (MF) patients. Methods: This Phase 1 trial evaluated cobomarsen given via intralesional injection (75 mg/dose), subcutaneous (SC), IV rapid bolus injection, or 2-hour IV infusion (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…A weekly dosing of at least 5 mg/kg was necessary to detect a significant effect on the target in humans [4]. Similar dose levels of cobomarsen, 300-900 mg/dose given on a weekly schedule, were used in a Phase 1 clinical trial of cutaneous T cell lymphoma patients [15]. The relatively high efficiency of MRG-110 in humans compared to other anti-miRs in humans is consistent with the preclinical finding that intracoronary infusion of 0.03-0.15 mg/kg anti-miR-92a (with the same formulation as MRG-110) in pigs increased the recovery after acute myocardial infarction [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A weekly dosing of at least 5 mg/kg was necessary to detect a significant effect on the target in humans [4]. Similar dose levels of cobomarsen, 300-900 mg/dose given on a weekly schedule, were used in a Phase 1 clinical trial of cutaneous T cell lymphoma patients [15]. The relatively high efficiency of MRG-110 in humans compared to other anti-miRs in humans is consistent with the preclinical finding that intracoronary infusion of 0.03-0.15 mg/kg anti-miR-92a (with the same formulation as MRG-110) in pigs increased the recovery after acute myocardial infarction [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although LNA-based anti-miRs have been shown to be safe and active in human studies of miravirsen, targeting a liver miRNA [4], as well as cobomarsen, targeting miR-155 in multiple hematological malignancies [15], little is known regarding the activity of other anti-miRs in humans. Studying anti-miR activity in humans is challenging, since the biological relevant targets often are regulated in organs, which are not easily accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Its proliferative inhibition was comparable to the effects observed by treating with bexarotene, a commonly prescribed rexinoid medication in CTCL [65]. Phase 1 trials were encouraging as they reported cobomarsen to be well tolerated with signs of a favorable clinical activity [112,113]. Studies are currently recruiting patients for phase 2 clinical trials in CTCL [112,113].…”
Section: Mir Targeted Therapymentioning
confidence: 96%
“…Based on the discussed literature, it is evident that miR-targeting drugs possess the potential to restore homeostasis of multiple oncogenic networks in CTCL. Indeed, preclinical validations of numerous miR drug candidates have been reported and early active phase trials of miR are currently being performed; however, phase 3 trials targeting miRs still remain to be initiated [83,100,112].…”
Section: Mir Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation